WEWENANG PERSERIKATAN BANGSA-BANGSA DALAM MENCEGAH DAN MEMBERIKAN TINDAKAN TERHADAP SEPARATISME - Ersyah Maulana Rahman, (2021)
Abstract Dissatisfaction with the government can lead to conflicts that have an impact on the number of victims, the conflict arises as a result of the separatist movement and it is the task of the United Nations as an International Organization that maintains world security and peace to overcome these problems, especially in cases of human rights violations. The formulation of the problem in this research is how the UN's authority is to prevent and resolve the problem of separatism in Indonesia and what impact it can have from solving the problem of separatism in Indonesia. This research uses normative juridical research. The results of this study show that the UN's authority is to intervene in the state with the consideration that human rights violations have occurred, send its investigative team to countries in conflict with the aim of finding causes and solutions that can resolve conflicts and mediate. conflict. The impact of solving the problem of separatism in Indonesia is the progress and development of infrastructure development, the economy in conflict areas, regional stability and security, and community welfare.